Browning mechanism in stems of fresh‑cut lettuce. (30th March 2023) - Zhang, Lin; Wang, Zhiqiang; Zeng, Shixian; Yuan, Shuzhi; Yue, Xiaozhen; Tian, Tian; Zhu, Xiaoqian; Zheng, Shufang; Xu, Xiangbin; Zuo, Jinhua; Wang, Qing
Highlights: Cellular fluids released from the cut stem are the primary cause of browning. Mass levels of ROS production have an indirect effect on stem browning. The browning of cellular fluids was mainly related to the PAL activity increased. The stem browning was related to unsaturated fatty acids content decreased. A sufficient supply of energy can maintain the activity of antioxidant enzymes. Abstract: Cellular fluids and latex released from cut cells in the stems of lettuce when it is harvested are the major source of stem browning. In the present study, the browning process of cellular fluids and latex released from romaine and iceberg lettuce stems was investigated. An increase in LOX enzyme and total phenolics also occurs during lettuce stem browning. A decrease in ascorbic acid content, an increase in phenylalanine ammonia lyase and lipoxygenase activity were important factors responsible for the browning. Metabolomic and proteomic analyses indicated that changes in the level of glutathione metabolism, indole alkaloid biosynthesis, oxidative phosphorylation, galactose metabolism were also associated with stem browning. The main causes of stem browning in fresh cut lettuce were comprehensively investigated in the present study and the resulting data provided information that can be used in the study of browning in lettuce and other vegetables during harvest or fresh-cut processing.